2013
DOI: 10.1016/s0034-7094(13)70224-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Lumbar Interspinous Spaces by Palpation and Verified by X-rays

Abstract: There was a discrepancy between the anesthesiologists' estimation by palpation and the actual catheter insertion level shown in X-rays. It seems to be safer to choose the interspinous level L3-4 or lower in spinal anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Traditional techniques, such as X-ray and ultrasound, have been investigated for the visual guidance of spinal puncture. Tanaka et al 19 found that the accuracy of puncture point location by X-ray guidance (67%) was better than that of the traditional anatomic localization approach (29-59%). However, the X-ray-guided spinal puncture technique is generally used only for patients in the prone position, while spinal anesthesia puncture requires the patient to be in the lateral decubitus or sitting position.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional techniques, such as X-ray and ultrasound, have been investigated for the visual guidance of spinal puncture. Tanaka et al 19 found that the accuracy of puncture point location by X-ray guidance (67%) was better than that of the traditional anatomic localization approach (29-59%). However, the X-ray-guided spinal puncture technique is generally used only for patients in the prone position, while spinal anesthesia puncture requires the patient to be in the lateral decubitus or sitting position.…”
Section: Discussionmentioning
confidence: 99%
“…Palpation may not be a reliable technique, with an error of one-third to identify the interspinous level in obstetric patients. 2 It seems to be safer for anesthesiologists to aim at L3-L4 interspinous level or lower in the intrathecal technique. The intervertebral needle insertion site that is usually targeted is the L3-L4 interspace, or less commonly, the L2-L3 interspace.…”
Section: Discussionmentioning
confidence: 99%
“…This might be caused by inadequate difference in lumbar vertebrae furtherance in both groups (15, 16). Many studies have found landmark identification to be one of the important factors for successful spinal anesthesia administration, although its accuracy in evaluating the required intervertebral gaps is poor (1, 4, 9, 25, 26). …”
Section: Discussionmentioning
confidence: 99%